2007
DOI: 10.1136/thx.2006.067868
|View full text |Cite
|
Sign up to set email alerts
|

Increased alveolar nitric oxide concentration and high levels of leukotriene B4 and 8-isoprostane in exhaled breath condensate in patients with asbestosis

Abstract: Background: Inhaled asbestos fibres can cause inflammation and fibrosis in the lungs called asbestosis. However, there are no non-invasive means to assess and follow the severity of the inflammation. Exhaled nitric oxide (NO) measured at multiple exhalation flow rates can be used to assess the alveolar NO concentration and bronchial NO flux, which reflect inflammation in the lung parenchyma and airways, respectively. The aim of the present study was to investigate whether exhaled NO or markers in exhaled breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 52 publications
(29 reference statements)
6
84
1
2
Order By: Relevance
“…In addition, cysteinyl LTs were elevated. Lehtonen 15) found increase of LT B4 in patients with asbestosis, which finding differed from our previous study in 92 asbestos-exposed subjects 17) , where about 76% of patients had pleural hyalinosis and 61% interstitial lung fibrosis. In contrast, in recent study, hyalinosis and/or asbestosis were present in all subjects.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In addition, cysteinyl LTs were elevated. Lehtonen 15) found increase of LT B4 in patients with asbestosis, which finding differed from our previous study in 92 asbestos-exposed subjects 17) , where about 76% of patients had pleural hyalinosis and 61% interstitial lung fibrosis. In contrast, in recent study, hyalinosis and/or asbestosis were present in all subjects.…”
Section: Discussioncontrasting
confidence: 56%
“…It was shown that patients with idiopathic pulmonary fibrosis exhibit overproduction of both LT B4 and cysteinyl LTs 13,14) . LT B4 15) and cysteinyl LTs were also elevated in the EBC of patients with pneumoconioses 16,17) .…”
Section: Introductionmentioning
confidence: 97%
“…EBC contains several bio- markers of inflammation and oxidative stress, and collection can be repeated several times without any adverse effects, even in children 6) or severely ill patients. 8-isoprostane has been observed to increase in the EBC of patients with idiopathic pulmonary fibrosis 7) and in our limited study with asbestos exposed subjects 8) ; it was recently confirmed in 15 patients with asbestosis, in parallel with the inflammation marker, alveolar nitric oxide concentration 9) . Because the effect of recent smoking, another source of reactive oxygen species on the concentrations of 8-isoprostane on breath condensate has been described 5) , cotinine, a metabolite of nicotine in the urine and a tobacco smoke biomarker 10) was also analyzed in our study to eliminate this possible influence.…”
Section: Introductionmentioning
confidence: 49%
“…In humans, determination of the concentration of 8-iso-prostaglandin F 2α (8-isoprostane) in exhaled breath condensate (EBC) has proven to be valuable in assessing oxidative stress. The analysis of this derivative of arachidonic acid, produced in free radical-catalyzed reactions, appears to be a promising non-invasive means for assessing the activity of both silica and asbestos-induced diseases [2][3][4] . Moreover, no effect of sex or smoking status was observed in these studies.…”
Section: Introductionmentioning
confidence: 99%